Does Cosmic-Ray-Induced Heterogeneous Chemistry Influence Stratospheric Polar Ozone Loss ? - Müller, R.; Grooß, J.-U. (Physical Review Letters, 2009)
Cosmic-ray (CR) -induced heterogeneous reactions of halogenated species have been suggested to play the dominant role in causing the Antarctic ozone hole. However, measurements of total ozone in Antarctica do not show a compact and significant correlation with CR activity. Further, a substantial CR-induced heterogeneous loss of chlorofluorocarbons is incompatible with multiyear satellite observations of N2O and CFC-12. Thus, CR-induced heterogeneous reactions cannot be considered as an alternative mechanism causing the Antarctic ozone hole.